Alfredo Torero y los avatares de una traducción. La obra de un gran lingüista universal - Sala Báez, Yolanda (2006)
This article is about the eminent Peruvian linguist Alfredo Torero’s last years in the Netherlands, as political refugee, and mentions various efforts deployed to get his masterpiece research: Idiomas de los Andes - Lingüística e Historia, translated into French.